2010
DOI: 10.1136/bmj.c4737
|View full text |Cite
|
Sign up to set email alerts
|

Reboxetine for acute treatment of major depression: systematic review and meta-analysis of published and unpublished placebo and selective serotonin reuptake inhibitor controlled trials

Abstract: Objectives To assess the benefits and harms of reboxetine versus placebo or selective serotonin reuptake inhibitors (SSRIs) in the acute treatment of depression, and to measure the impact of potential publication bias in trials of reboxetine. Design Systematic review and meta-analysis including unpublished data. Data sources Bibliographic databases (Medline, Embase, PsycINFO, BIOSIS, and Cochrane Library), clinical trial registries, trial results databases, and regulatory authority websites up until February 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
217
5
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 477 publications
(238 citation statements)
references
References 43 publications
3
217
5
13
Order By: Relevance
“…This is despite empirical data suggesting that conclusions of systematic reviews can change when unpublished data are used. A classic example is the review of reboxetine, where publication bias has been clearly demonstrated (29,30) Although some systematic reviewers in this cohort contacted manufacturers, the decline in reviewers contacting manufacturers is of great concern and requires research into the reasons. This may ironically be a result of the recent publicity on the difficulties experienced by reviewers when attempting to obtain unpublished data from manufacturers (31) and the very long delays before a response is received (32), or with such small numbers may not be an overall trend.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…This is despite empirical data suggesting that conclusions of systematic reviews can change when unpublished data are used. A classic example is the review of reboxetine, where publication bias has been clearly demonstrated (29,30) Although some systematic reviewers in this cohort contacted manufacturers, the decline in reviewers contacting manufacturers is of great concern and requires research into the reasons. This may ironically be a result of the recent publicity on the difficulties experienced by reviewers when attempting to obtain unpublished data from manufacturers (31) and the very long delays before a response is received (32), or with such small numbers may not be an overall trend.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Pharmaceutical company sponsors o en do not submit the results of negative drug trials for publication (11)(12)(13) and may downplay adverse events (14,15). Selective reporting of clinical trial results can yield awed estimates of drug e ectiveness and provide an erroneous impression of the risk-bene t ratio of treatments, leading physicians to make inappropriate prescribing decisions (16).…”
Section: Publication Biasmentioning
confidence: 99%
“…2 Publication bias in medical research continues to be a problem today, as shown by a recent meta-analysis which compared the effectiveness of reboxetine with selective serotonin reuptake inhibitors (SSRI) or placebo for treating major depression. 8 The investigators found that 74% of data were not published and 'published data overestimated the benefit of reboxetine versus placebo by up to 115% and reboxetine versus SSRIs by up to 23%, and also underestimated harm'. 8 Previous findings of reboxetine's effectiveness were reversed.…”
mentioning
confidence: 99%
“…8 The investigators found that 74% of data were not published and 'published data overestimated the benefit of reboxetine versus placebo by up to 115% and reboxetine versus SSRIs by up to 23%, and also underestimated harm'. 8 Previous findings of reboxetine's effectiveness were reversed.…”
mentioning
confidence: 99%
See 1 more Smart Citation